High‐Performance Integrated Perovskite and Organic Solar Cells with Enhanced Fill Factors and Near‐Infrared Harvesting. Issue 16 (24th February 2016) - Kim, Junghwan; Kim, Geunjin; Back, Hyungcheol; Kong, Jaemin; Hwang, In‐Wook; Kim, Tae Kyun; Kwon, Sooncheol; Lee, Jong‐Hoon; Lee, Jinho; Yu, Kilho; Lee, Chang‐Lyoul; Kang, Hongkyu; et al.
Abstract : Highly efficient P‐I‐N type perovskite/bulk‐heterojunction (BHJ) integrated solar cells (ISCs) with enhanced fill factor (FF) (≈80%) and high near‐infrared harvesting (>30%) are demonstrated by optimizing the BHJ morphology with a novel n‐type polymer, N2200, and a new solvent‐processing additive. This work proves the feasibility of highly efficient ISCs with panchromatic absorption as a new photovoltaic architecture and provides important design rules for optimizing ISCs.